Novel Insights into the Antimicrobial and Antibiofilm Activity of Pyrroloquinoline Quinone (PQQ); In Vitro, In Silico, and Shotgun Proteomic Studies - Mai M. Labib; Alaa M. Alqahtani; Hebatallah H. Abo Nahas; Rana M. Aldossari; Bandar Fahad Almiman; Sarah Ayman Alnumaani; Mohammad El-Nablaway; Ebtesam Al-Olayan; Maha Alsunbul; Essa M. Saied (Biomolecules, 2024)
Microbial infections pose a significant global health threat, affecting millions of individuals and leading to substantial mortality rates. The increasing resistance of microorganisms to conventional treatments requires the development of novel antimicrobial agents. Pyrroloquinoline quinone (PQQ), a natural medicinal drug involved in various cellular processes, holds promise as a potential antimicrobial agent. In the present study, our aim was, for the first time, to explore the antimicrobial activity of PQQ against 29 pathogenic microbes, including 13 fungal strains, 8 Gram-positive bacteria, and 8 Gram-negative bacteria. Our findings revealed potent antifungal properties of PQQ, particularly against Syncephalastrum racemosum, Talaromyces marneffei, Candida lipolytica, and Trichophyton rubrum. The MIC values varied between fungal strains, and T. marneffei exhibited a lower MIC, indicating a greater susceptibility to PQQ. In addition, PQQ exhibited notable antibacterial activity against Gram-positive and -negative bacteria, with a prominent inhibition observed against Staphylococcus epidermidis, Proteus vulgaris, and MRSA strains. Remarkably, PQQ demonstrated considerable biofilm inhibition against the MRSA, S. epidermidis, and P. vulgaris strains. Transmission electron microscopy (TEM) studies revealed that PQQ caused structural damage and disrupted cell metabolism in bacterial cells, leading to aberrant morphology, compromised cell membrane integrity, and leakage of cytoplasmic contents. These findings were further affirmed by shotgun proteomic analysis, which revealed that PQQ targets several important cellular processes in bacteria, including membrane proteins, ATP metabolic processes, DNA repair processes, metal-binding proteins, and stress response. Finally, detailed molecular modeling investigations indicated that PQQ exhibits a substantial binding affinity score for key microbial targets, including the mannoprotein Mp1P, the transcriptional regulator TcaR, and the endonuclease PvuRTs1I. Taken together, our study underscores the effectiveness of PQQ as a broad-spectrum antimicrobial agent capable of combating pathogenic fungi and bacteria, while also inhibiting biofilm formation and targeting several critical biological processes, making it a promising therapeutic option for biofilm-related infections.